Elevation effects on the carbon budget of tropical mountain forests (S Ecuador): The role of the belowground compartment - Moser, G; Leuschner, C; Hertel, D.; Graefe, Sophie; Soethe, N; Iost, S (Wiley, 2011)
Carbon storage and sequestration in tropical mountain forests and their dependence on elevation and temperature are not well understood. In an altitudinal transect study in the South Ecuadorian Andes, we tested the hypotheses that (i) aboveground net primary production (ANPP) decreases continuously with elevation due to decreasing temperatures, whereas (ii) belowground productivity (BNPP) remains constant or even increases with elevation due to a shift from light to nutrient limitation of tree growth. In five tropical mountain forests between 1050 and 3060 m a.s.l., we investigated all major above- and belowground biomass and productivity components, and the stocks of soil organic carbon (SOC). Leaf biomass, stemwood mass and total aboveground biomass (AGB) decreased by 50% to 70%, ANPP by about 70% between 1050 and 3060 m, while stem wood production decreased 20-fold. Coarse and large root biomass increased slightly, fine root biomass fourfold, while fine root production (minirhizotron study) roughly doubled between 1050 and 3060 m. The total tree biomass (above- and belowground) decreased from about 320 to 175 Mg dry mass ha?1, total NPP from ca. 13.0 to 8.2 Mg ha?1 yr?1. The belowground/aboveground ratio of biomass and productivity increased with elevation indicating a shift from light to nutrient limitation of tree growth. We propose that, with increasing elevation, an increasing nitrogen limitation combined with decreasing temperatures causes a large reduction in stand leaf area resulting in a substantial reduction of canopy carbon gain toward the alpine tree line. We conclude that the marked decrease in tree height, AGB and ANPP with elevation in these mountain forests is caused by both a belowground shift of C allocation and a reduction in C source strength, while a temperature-induced reduction in C sink strength (lowered meristematic activity) seems to be of secondary importance.